"If You Become Naked": Sexual Honesty on the Beatles' White Album. Issue 3 (1st September 2020) - Kapurch, Katie; Everett, Walter
ABSTRACT: The Beatles' White Album is a musical expression of getting naked, revealing anxiety and doubt in songs that fetishize objects and role play while representing impotence and cuckolding. Anxiety and ambivalence about sexual performance track alongside other attitudes toward time, including nostalgia about the past and an ineffectual desire to move forward, that have biographical significance for the Beatles in 1968. The sexually honest double album strips off the psychedelia of the previous year, and The White Album 's unifying theme is, in fact, voiced explicitly on the record itself – not by a Beatle, but by Yoko Ono.